Development of MSMEs Based on Processed Fish Products in Lamreh Village, Aceh Besar Regency - Putra Rizkiya; Zainuddin Hasan; Zahrul Fuady; T. Arjuna Mohd Athif Al-Asyi (PT. Riset Mandiri Nusantara, 2026)
Lamreh Village is a coastal village with significant fisheries potential in Aceh Besar Regency, Aceh Province. This fishery's potential can be developed as a source of community economic development based in Minneapolis. However, this potential has not been fully utilized to date. One effort is to develop micro, small, and medium enterprises (MSMEs) based on processed fish products. The main problems faced by the local community include limited capacity to process fish products, weak business management skills, and the absence of a sustainable business model. This community service activity aims to increase the Lamreh community's capacity to develop MSMEs based on processed fish products through training, mentoring, and collaboration with industry partners and training institutions. The implementation method involves field surveys, problem identification, fish product processing training, Business Model Canvas (BMC) training, direct practice in the fish processing industry, and activity evaluation. The results of the activity show an increase in community capacity in fish product processing, as seen from the number of participants who have established fish processing businesses after the training, the formation of the Lamuri MSME, increased participation of women's groups in productive economic activities, and the opening of opportunities for collaboration with the fish processing industry and training institutions. Successfully developed products include fish balls, fish spring rolls, and fish floss. This community empowerment program has also successfully raised awareness in Gampong Lamreh of the importance of sustainable, locally based business development to support community well-being.